Determination of Antioxidant and Anticancer Activities together with Total Phenol and Flavonoid Contents of Cleidion javanicum Bl. and Bridelia retusa (L.) A. Juss. - Duangsuree Sanseera (Science Faculty of Chiang Mai University, 2019)
The antioxidant and anticancer activities of the hexane, chloroform and methanol extracts of the leaves, stems and fruits from Cleidion javanicum Bl. and Bridelia retusa (L.) A. Juss. were investigated. The antioxidant activities were evaluated by DPPH and ABTS methods. The methanol extracts of the stems and fruits from B. retusa and the methanol extract of the leaves from C. javanicum showed the highest antioxidant activity. The methanol extract of the leaves from B. retusa possessed significant anticancer activity against KB-Oral cavity cancer (IC50 = 21.24 µg/mL), MCF-7 breast cancer cell (IC50 = 17.81 µg/mL), and NCI-H 187 – small cell lung cancer (IC50 = 24.24 µg/mL), whereas the methanol extract of the fruits exhibited the highest anticancer activity against NCI-H 187 – small cell lung cancer with an IC50 value of 8.21 µg/mL. The hexane extract of the fruits from C. javanicum showed significant anticancer activity against NCI-H 187 – small cell lung cancer with an IC50 value of 29.11 µg/mL. All of the extracts of these two medicinal plants were non-cytotoxic to primate cell line (Vero cell). Quantitative determination of phenols and flavonoids in leaves, stems and fruits extracts from B. retusa and C. javanicum was carried out using spectrophotometric methods. The methanol extract of B. retusa fruits and the methanol extract of C. javanicum stems contained the highest phenolic content. The methanol extract of B. retusa leaves contained maximum flavonoid, whereas the chloroform extract of C. javanicum leaves contained maximum flavonoid. These two plants may play important roles for the production of health supplement and might be led to the isolation of lead compounds for drug development.